Isolation and Identification of Free Radical Scavenging Compound from Stem Bark Soursoup (Annona muricata L.) Extract - Mentarry Bafadal; A Amaliah Dahlia; Ahmad Najib (Faculty of Pharmacy, Universitas Muslim Indonesia, 2020)
Isolation and Identification of free radical active compound from stem bark soursoup (Annona muricata L.) extract. The aim of this research is to observe the chemical compound of stem bark the soursoup (A. muricata L.) which is active as a free radical. 550 gram of stem bark the soursoup (A. muricata L.) was by graduate extracted using n-heksan, ethyl acetat and ethanol solvents respectively. Extract result is the extraction, it was produced 2.4 gram n-heksan extract, 8.4 gram ethyl acetat extract, 2.1 gram ethanolic extract. The isolation of ethyl acetat extract was conducted using colom chromatography (TLC) method using eluent n-hexane : ethyl acetat (7:3) and it was produced four fractions. The third fraction was isolated using preparative thin layer chromatography with mob ile phase n-hexane : ethyl acetat (6:1) and got 2 bands. The isolate identified by UV-Vis spectroscopy, IR spectroscopy and analyzed by chemistry reaction. From the data result show that isolate is acetogenin.